Effect of post-weld solution treatment on microstructure and mechanical properties of electron beam welded IN738LC joint - Houqin Wang; Ke Han; Binggang Zhang (Journal of Materials Research and Technology, 2021)
The effect of post-weld solution treatment (PWST) on microstructure and mechanical properties of electron beam welded IN738LC joint has been investigated. The fusion zone (FZ) of IN738LC joint consisted of γ-Ni matrix, fine γʹ particles, granular MC carbides and a bit of M23C6 carbides after PWST. With the increased solution temperature, the area percent of MC carbides decreased while the content of γʹ particles increased gradually. The solvus temperature of γʹ phase in FZ and base metal (BM) was 1150 °C and 1175 °C, respectively, which was due to the different size of primary γʹ particles. When the complete dissolution of primary γʹ particles in FZ and BM occurred, the micro-hardness of FZ and BM reached the peak values (509.5 HV and 503.9 HV). As the solution temperature increased, the tensile strength of IN738LC joint initially increased and then decreased, while the stress-rupture life of IN738LC joint decreased steadily. The joint with bimodal-size γ′ particles and moderate MC carbides after 1125 °C/2 h heat treatment showed the excellent comprehensive mechanical performance, and the average strength and stress-rupture life of IN738LC joints were 686 MPa (900 °C) and 2.395 h (900 °C/350 MPa), respectively. Consequently, 1125 °C/2 h has been proposed as an optimized PWST process for IN738LC joint.